Limbah Partikel Keramik Platinum dan Kaca Lampu Clear Philips sebagai Additive Semen Pengeboran ditinjau Compressive Strength, Shear Bond Strength, dan Thickening Time - Ilcham, Adi; Awlia, Nur Risa (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
Ceramic and glass particle waste is generated in large quantities as a result of their extensive use in various applications. Inappropriate disposal of the waste can lead to environmental degradation and health hazards. This research utilizes ceramic and glass wastes as drilling cement additives in the oil and gas industry. The objective of this research is to study the effect of adding ceramic and glass waste on the properties of drilling cement, including compressive strength, shear bond strength, and thickening time. With composition percentage ratios of 10%, 20%, 30%, 35%, and 40% by weight of cement, the slurry was poured into 1.2x2 inch cubic molds to test compressive strength and into 1.2x2 inch cylindrical molds to test shear bond strength. The findings of this study indicate that the addition of ceramic and glass waste as a drilling cement additive has a positive effect on compressive strength, shear bond strength, and thickening time and is also effective for use as an alternative additive in drilling cement operations